Britain's Chinese eye : literature, empire, and aesthetics in nineteenth-century Britain - Chang, Elizabeth Hope (Stanford University Press, 2010)
This book traces the intimate connections between Britain and China throughout the nineteenth century and argues for China's central impact on the modern British visual imagination through a study of gardens, blue and white willow plates, the opium den, and the photograph, and literary texts.